Equipment failure: conducts of nurses and implications for patient safety - Gabriella da Silva Rangel Ribeiro; Rafael Celestino da Silva; Márcia de Assunção Ferreira; Grazielle Rezende da Silva; Juliana Faria Campos; Bianca Ribeiro Porto de Andrade
ABSTRACT Objectives: To identify equipment failures during handling by nurses and analyze the conduct of the professionals when these failures occur. Methods: Descriptive, exploratory and qualitative study, whose field was the intensive care unit of a public institution, and the participants were day nurses that worked providing direct care to patients. Data were produced in 2014 through systematic observation and interviews and were examined with thick description and content analysis. Results: The outcomes evinced the inadequate functioning of infusion bombs, users' errors related to the design of equipment and problems with batteries of artificial fans. These failures related to the management of equipment in the unit. Final considerations: It is necessary to strengthen the monitoring systems of safety conditions of equipment in intensive nursing care to prevent incidents.